Case report: Emerging therapies for transformed small cell lung cancer: efficacy of serplulimab and a comprehensive case report - Lyu, Heng-Xu; Ma, Wen-Hua; Zhang, Yong-Qian; Jin, Hui; Wang, Yu-Dong; Zhao, Min (Frontiers in Medicine, 2024)
This research reports a case of histological transformation from non-small cell lung cancer (NSCLC) to transformed small cell lung cancer (T-SCLC) in a patient undergoing EGFR-tyrosine kinase inhibitors (TKIs). The aggressive characteristics of the tumor diverged significantly from those commonly associated with lung adenocarcinomas, leading to further histological analysis. The subsequent histological examination confirmed the transformation to SCLC, consistent with established mechanisms of acquired resistance in NSCLC. Given the limited therapeutic options, the patient was administered a serplulimab-based immunochemotherapy regimen, achieving a progression-free survival (PFS) of 6 months post-transformation. The study underscores the potential of PD-1 inhibitors, particularly serplulimab, in the treatment landscape for T-SCLC and highlights the need for future comprehensive research.